Pattern and outcome of motorcyclists head injury in Ilorin, Nigeria - Yusuf, Ayodeji; Odebode, Timothy; Adeniran, James; Salaudeen, Adekunle; Adeleke, Nurudeen; Alimi, Mustapha (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background: Head injuries are a leading cause of death and morbidity among motorcycle users.Objectives: To determine the pattern, severity and outcome of motorcyclists' head injury presenting to our facility over 12 months.Materials and Methods: We prospectively studied 104 consecutive head injured motorcyclists using a predesigned questionnaire.Results: Seventy per cent of our patients were young adult males. Motorcycle versus other vehicle collision (49%) was the commonest mechanism of injury followed by lone cycle crash (26.0%). Only six motorcyclists, who were all riders (5.8%), wore crash helmet at the time of the crash. Brain contusions (33.3%) and intra-cerebral haematomas (26.7%) were the leading intracranial lesions. Seventy-eight percent of the patients suffered associated injuries, including face (63%) and extremities (24%). Mortality rate from lone crash was 37%, followed closely by motorcycle-vehicular collision.Conclusion: Outcome of head injury was significantly predictable by the nature of intracranial pathology and injury severity score (P= 0.000), being more favourable in younger age group, patients with normal brain computed tomography (CT) scan and those with extra-dural haematoma. Outcome was less favourable in patients with severe head injury, acute subdural haematoma and multiple intracranial haematomas.
Keywords: Head head injury; motorcycle; outcome; pattern